MINIMALS SECURITY HOUSE IN YOGYAKARTA - Bambang Sugestiyadi (Jurnal Penelitian Saintek, 2007)
Yogyakarta   could  be  the  mirror  of "Nusantara"    since  it had  been accumulated    with people  from "all around   the Nusantara  for  study. Yogyakarta  could  be considered   a town  which  would  grow  as  "Semi Metropolis"   city. there for physical  facilities   are needed.  This research was  conducted   to know  the minimalism   architecture   development   in house development  in Yogyakarta.The research  was  carried  out  on qualitative   design.  Data  collectedwith  observation,   visualization,   skates   maker, photo   documentation and  deeply  and structurally.   interview  Relevant   documentation   from some  conected  departments   was taken.  Data  analyzed  with inductive method.  It means  that  all data  not  to reveal  hypothesis   but focus   on abstract formation   based on parts  which were collected,  than grouped. Triangulation  was conducted for  testing data validity.The  results  showed  that:  (a) House   and  housing   development   until2004 decade  still dominated  by Mediteran  Style,  Tropical House  Style, Classical  House Style with ornamens,  (b) The Minimalism  House  Style in  architecture   focuses    on   essential    and  functional     things.    The Minimalism   Style dominated  by elementary  geometrical  form  without ornamen  or decoration,  and it became  its character.  It began  to grow since 2004 to 2006, in Sleman Regency,  Yogyakarta.